Disobedient Bodies in Digital Surveillance: V for Vendetta as a Holy Grail of Political Agency - Shumaila Noreen; Dr. Rasib Mahmood; Shahida Riaz (Journal of Management Practices, Humanities and Social Sciences, 2022)
Foucault’s notion of surveillance and panoptic gaze is notoriously implied in postmodernist discourse to exercise control and turn individual minds into docile automatic subjects. Both these concepts assert that power and knowledge are produced by the dominant center to demolish self-respect and promises absolute subjugation. This study aims at investigating the relevance of postmodern narratives in questioning the dictatorial as well as despotic role of capitalist powers and the repercussions it can have on individuals. The current research argues that power can also emanate from the periphery to counter the overarching hegemonic notions of authoritative control. Through a detailed analysis of visual narrative, i.e., V for Vendetta, the study revolves around the discursive nature of digital surveillance and the upholding of revolutionary libertarian thoughts and claims that an extreme discipline can lead to extreme forms of disobedience and resistance amongst masses. Foucault’s revolutionary idealism of V in Guy Fawkes Mask is an epitome of universalizing proclivity for political agency and freedom of thought. By employing qualitative research methodology, the study makes an in-depth content analysis of the movie, i.e., V for Vendetta. The research contributes to the literary corpus by digging deep in the implications and repercussions that digitalization of everyday life may result into. The uses of e-governance, though practical, can result in suppression and totalitarian governments. Although the subversion of ideological-cum-institutional repression at the cost of life and self seems deflating, the masses all disguised in mask highlights their anonymity and collective resistance towards the attainment of a utopian world.